Association of Antiplatelet Type on Length of Stay and Neurological Outcomes in Ischemic Stroke - Aprillia Wardhani, Firdha (Brawijaya University, 2025)
Antiplatelet therapy plays an important role in preventing the progression of ischemic stroke. However, the effectiveness of different types of antiplatelet agents in improving clinical outcomes still requires further investigation. This study aimed to analyze the relationship between the type of antiplatelet used and the clinical outcomes of hospitalized ischemic stroke patients, based on changes in the National Institutes of Health Stroke Scale (NIHSS) score and length of stay (LoS). This research was a retrospective cross-sectional observational study involving 92 hospitalized patients with ischemic stroke. Patients were grouped based on the antiplatelet therapy received: Clopidogrel (CPG) (n=58), Aspirin (n=17), and dual antiplatelet therapy (DAPT) with Clopidogrel + Aspirin (n=17). Of the total patients, 43 (46.7%) showed improvement in NIHSS score, while 49 (53.2%) did not. The mean LoS was 7.033 days. The proportion of patients with NIHSS improvement by treatment group showed that the CPG group had the highest percentage of improvement, with 30 out of 58 patients (51.72%), compared to Aspirin 7/17 (41.2%) and DAPT 6/17 (35.3%). However, statistical analysis revealed no significant association between the type of antiplatelet and NIHSS improvement (p = 0.431). In addition, Kruskal-Wallis analysis revealed no significant association between LoS and antiplatelet type (p = 0.429). These findings suggest that other factors may play a more substantial role in determining the clinical outcomes of ischemic stroke patients. Keywords: antiplatelet, clinical outcome, NIHSS, ischemic stroke, LoS